Comparative efficacy between ketamine, memantine, riluzole and d-cycloserine in patients diagnosed with drug resistant depression: a meta-analysis - Darji, Nishita H.; Rana, Devang A.; Malhotra, Supriya D. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Glutamate modulators are having immense potential and are newer entities for treating drug resistant depression. The objectives were to generate statistical evidence on basis of existing data of ketamine, memantine, riluzole and d-cycloserine in resistant depression. Methods: A total of 14 RCTs following PRISMA guidelines and matching inclusion and exclusion criteria were collected of ketamine (5), memantine (3), riluzole (2) and d-cycloserine (4) vs placebo in drug resistant depression. Only RCTs with primary diagnosis of drug resistant depression (Previously on two standard antidepressant therapy) were included. Studies with treatment response rate, 50% reduction in total score of the depression rating scale-Montgomery-Åsberg Depression Rating Scale or the Hamilton Depression Rating Scale or Beck Depression Inventory was chosen as clinical outcome measure. RevMan 5.3 software was used for the analysis. Results: In ketamine group using random effect model SMD was 2.122 (95% CI 0.659-3.584). P-value was statistically significant (random effect p <0.005 and in fixed effect <0.001). In memantine group, using random effect model -0.963 was SMD and (95% CI -1.958-0.0324). P-value was <0.001, significant in fixed effect. In riluzole group, SMD was -0.564 with (95% CI -3.927-2.799) in random effect. P-value was 0.741. In d-cycloserine group SMD was 0.316 with (95% CI -1.252-1.885) in random effect. P-value was 0.690. Conclusions: Ketamine showed best efficacy followed by memantine. Riluzole and DCS as such have no efficacy although its acts by same glutamate pathway. More molecular based research is required in use of glutamate modulators in resistant depression.